ANALISIS KEPUASAN MAHASISWA TERHADAP KUALITAS LAYANAN (SERVICE QUALITY) FAKULTAS TEKNOLOGI INFORMASI UNIVERSITAS STIKUBANK SEMARANG - Mariana, Novita; Sriartati Redjeki, Rara; Purwatiningtyas, Purwatiningtyas (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
The purpose of this research is to analyze the level of student satisfaction with the quality of service in the Information Technology Faculty of the University of Stikubank Semarang. From the results of observations and interviews, 5 variables were obtained, namely Lecturer, BAK, Infrastructure, Lectures, and Image / Brand Image where the items in each measuring variable used the SERQUAL dimension. The sample of respondents was selected as many as 30 final semester students who have completed their thesis. The instrument is declared valid with a KMO value greater than the test value of 0.5 and reliable with a Cronbrach’s Alpha value greater than the 0.6 test value using SPSS 19. The results of the value of the student satisfaction index (Customer Satisfaction Index) are 78.4% which means The faculty is able to provide satisfactory service quality to students. From the IPA quadrant, it is found that infrastructure and lectures are in quadrant II (Priority Priority) where on average these variables are perceived to be very important by students and faculty have carried out the level of service performance as expected by students.